Unusual Ventriculo-Arterial Alignments and Connections. Issue 3 (May 2020) - Sanders, Stephen P.; Toba, Shuhei
In this issue of World Journal for Pediatric and Congenital Heart Surgery, Kari and colleagues present a case of anatomically corrected malposition S, L, L with ventricular septal defect and complex subaortic stenosis managed by staged biventricular repair. This rare case with interesting management strategy provides an opportunity to clarify this and related unusual ventriculo-arterial alignments.